ANALYSIS OF THE STYLISTIC POETRY ‘TUHAN, KITA BEGITU DEKAT – GOD, WE ARE SO CLOSED’ BY ABDUL HADI W.M - S. Samsuddin (Universitas Sembilanbelas November Kolaka, 2016)
Stylistic or style as the author’s personal expression of quality in the creation of poetry. The quality of personality obtained through universality. The intensity found on the thoroughness, accuracy, and emotional Crystallization, not an intellectual. The quality of the personality of the poet used as the characteristic of the poet in creating poetry. The problem studied in this research is How is stylistic poetry by Abdul Hadi W.M? This study aimed to describe the analysis of the stylistic poems by Abdul Hadi WM benefit expected in this study were (a) theoretically, this study is helpful to the development of literary theory, especially the theory of poetry and stylistic. (B) practical research Translation ( 1) researchers and readers can obtain in-depth description of the analysis of the stylistic poems Abdul Hadi WM (2) source of referral for further research and as a reference source of learning materials Indonesian language and literature especially learning poetry. (3) educational institutions can make the results of research this as a reference to the development of theories of literature, especially poetry stylistic analysis by Abdul Hadi. This study is a literature research using descriptive research design. Sources of data in this study are a collection of poetry Horison Indonesian Literature, poetry internationally 2002. The data is text (lines and stanzas) that contain stylistic poetry. Data was collected by using read and record technique. Data were analyzed by using the theory of stylistic, with the objective approach. The results showed a significant choice of words connotation dominate poems by Abdul Hadi W.M. Meaningful words used connotation poet to style or personal characteristic (idiosyncrasy) poet, style or technique of exposition and style or technique of the highest quality literary achievement that is used to reach the top aesthetic poet poetry. The imagery are dominated by the image of feelings. The imagery feelings become style or characteristic (idiosyncrasy) personal, style or technique exposition technique and style or quality of the highest literary achievement. The sound is dominated by the sound of Kakafoni. This sound becomes a style or personal characteristic (idiosyncrasy), style or technique or style of exposition and literary quality engineering achievement. Theme options divinity of Tuhan, Kita Begitu Dekat in the poetry becomes a style or personal characteristic (idiosyncrasy), style or technique of exposition, style or quality of the highest literary achievement.